New Insights into the Loss of Antioxidant Effectiveness of Phenolic Compounds in Vegetable Oils in the Presence of Phosphatidylcholine - Joaquín Velasco; María-Jesús Gil; Yun-Qi Wen; Aída García-González; María-Victori (MDPI AG, 2023)
It has been proposed that lipid oxidation reactions in edible oils primarily occur in reverse micelles (RM) of amphiphilic components. While the prooxidative effect of RM has been demonstrated, the mechanism involved is not fully understood. Both reductions and enhancements in the antioxidant efficacy (AE) of α-tocopherol and Trolox have been observed in different studies when phosphatidylcholine (PC) was added and PC RM were formed. However, most of these investigations employed lipid systems consisting of stripped vegetable oil diluted in saturated medium-chain triacylglycerols (MCT) and utilized antioxidant concentrations well below those found in edible oils. These two specific factors were investigated in the present study. The effect of RM of purified egg yolk PC on the AE of 1.16 mmol kg−1 α-tocopherol or Trolox in stripped sunflower oil (SSO) was studied by the Rancimat (100 °C) and oven (50 °C) tests. Increasing PC concentrations (50-1000 ppm) had no significant impact on α-tocopherol, but substantial reductions in AE were observed for Trolox. This phenomenon may be attributed to the partitioning of Trolox into the pre-existing PC micelles, suggesting that primary oxidation reactions occurred in the continuous lipid phase. In addition, the effectiveness of both antioxidants decreased significantly in the presence of PC when a low antioxidant concentration (0.06 mmol kg−1) was assayed in SSO:MCT (1:3, w/w).